Partisipasi Masyarakat dalam Pengembangan Desa Wisata Timpag - Devi Udayani, Ni Putu; Diah Utari Dewi, Nyoman; Ayu Sri Widnyani, Ida (Universitas Ekasakti, 2024)
This research aims to explore the level of community participation in the development of Timpag Tourism Village. Data collection was conducted through qualitative methods with in-depth interviews and participatory observation. The results show that community participation in the development of Timpag Tourism Village is at a fairly high level, characterized by active involvement in various development activities and tourism management. Factors that encourage participation include awareness of the economic, social and cultural benefits derived from tourism activities. However, there are several barriers such as limited human resources and support from the government that still need to be improved. Recommendations include increasing community capacity through training and increasing cooperation between the community and the government and the private sector.